A constitutively active mutant beta 2-adrenergic receptor is constitutively desensitized and phosphorylated. - Pei, G (1994)
The beta 2-adrenergic receptor (beta 2AR) can be constitutively activated by mutations in the third intracellular loop. Whereas the wild-type receptor exists predominantly in an inactive conformation (R) in the absence of agonist, the mutant receptor appears to spontaneously adopt an active conformation (R*). We now demonstrate that not only is the mutant beta 2AR constitutively active, it is also constitutively desensitized and down-regulated. To assess whether the mutant receptor can constitutively engage a known element of the cellular desensitization machinery, the receptor was purified and reconstituted into phospholipid vesicles. These preparations retained the essential properties of the constitutively active mutant receptor: agonist-independent activity [to stimulate guanine nucleotide-binding protein (Gs)-GTPase] and agonist-specific increase in binding affinity. Moreover, the purified mutant receptor, in the absence of agonist, was phosphorylated by recombinant beta AR-specific kinase (beta ARK) in a fashion comparable to the agonist-occupied wild-type receptor. Thus, the conformation of the mutated receptor is equivalent to the active conformation (R*), which stimulates Gs protein and is identical to the beta ARK substrate.